Individual expression patterns of myotoxin isoforms in the venom of the snake Bothrops Asper. - Carmona Morera, Elena (1992)
In order to investigate the distribution of myotoxin isoforms in the snake Bothrops asper, venoms from individual specimens were analyzed by a cathodic electrophoretic system for basic proteins under native conditions.The electrophoretic system resolved at least five bands with slight differences in mobility, corresponding to the fastest migrating proteins in the venom. The identity of the bands was confirmed by immunoblotting, using a rabbit anti-myotoxin serum.There were clear differences in the individual patterns of myotoxin isoform expression, both in specimens from the Atlantic and Pacific regions of Costa Riea. Some individuals possessed all five variants. In agreement with previous reports, the venoms of ten newborn (less than I0 days of age) specimens completely lacked myotoxin bands, indicating an ontogenetic regulation in the expression of these toxins in B. asper. One of the bands, corresponding to the lysine-49 phospholipase myotoxin II, was the only isoform present in all individuals studied, suggesting a possible selective pressure for the conservation of this type of protein in the venom of B. asper.